Analisis Financial Distress menggunakan Model Altman Z-Score Modifikasi pada PT Garuda Indonesia (Persero) Tbk. Periode 2021–2025 - Fatma Dwi Jati; Jojor Lisbet Sibarani; Susilawati Susilawati; Cahyo Ginarti; Rehulina Bangun (Journal of Management and Creative Business, 2026)
This study aims to analyze the financial distress condition of PT Garuda Indonesia (Persero) Tbk during the period of 2021–2025 using the modified Altman Z-Score model. This research employs a quantitative approach using secondary data in the form of financial statements obtained from the company’s official website. The analytical method used is descriptive analysis by calculating financial ratios, including working capital to total assets (X1), retained earnings to total assets (X2), earnings before interest and tax to total assets (X3), and book value of equity to book value of total debt (X4). The results indicate that the Z-Score values of PT Garuda Indonesia (Persero) Tbk throughout the study period fall within the distress zone. This condition suggests that the company is experiencing significant financial pressure and has a high risk of potential bankruptcy. Although there are indications of improvement in several financial ratios in recent years, the overall financial condition of the company remains unstable. These findings are expected to provide insights for management in formulating financial recovery strategies and for investors in making informed decisions.